2010
DOI: 10.1128/mcb.00919-09
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Hop1 and Mek1 in Meiotic Chromosome Pairing and Recombination Partner Choice in Schizosaccharomyces pombe

Abstract: Synaptonemal complex (SC) proteins Hop1 and Mek1 have been proposed to promote homologous recombination in meiosis of Saccharomyces cerevisiae by establishment of a barrier against sister chromatid recombination. Therefore, it is interesting to know whether the homologous proteins play a similar role in Schizosaccharomyces pombe. Unequal sister chromatid recombination (USCR) was found to be increased in hop1 and mek1 single and double deletion mutants in assays for intrachromosomal recombination (ICR). Meiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 73 publications
3
71
0
Order By: Relevance
“…We furthermore revealed that DMC1-coated nucleoprotein filaments are in principle competent to repair from both sister chromatids and homologous chromosomes. In the wild type, they are impeded from accessing the sister chromatid, presumably by locally activated ASY1 (Hop1), consistent with earlier reports from yeasts (Niu et al, 2005;Carballo et al, 2008;Goldfarb and Lichten, 2010;Latypov et al, 2010). Building on these earlier reports, we infer that this local, DSB-dependent activation is mediated by ATM, because the interhomolog bias of meiotic DNA repair is still intact in atr rad51 mutants.…”
Section: Discussionsupporting
confidence: 76%
“…We furthermore revealed that DMC1-coated nucleoprotein filaments are in principle competent to repair from both sister chromatids and homologous chromosomes. In the wild type, they are impeded from accessing the sister chromatid, presumably by locally activated ASY1 (Hop1), consistent with earlier reports from yeasts (Niu et al, 2005;Carballo et al, 2008;Goldfarb and Lichten, 2010;Latypov et al, 2010). Building on these earlier reports, we infer that this local, DSB-dependent activation is mediated by ATM, because the interhomolog bias of meiotic DNA repair is still intact in atr rad51 mutants.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, the recombination reductions may be a consequence of the early role of Mek1 in DSB formation as reported by others. 15,36 Taken together, we conclude that Mek1 plays multiple roles; phosphorylation of Mek1-T15 is important for proper progression of early meiosis including initiation of meiotic S phase, while the kinase and FHA domains of Mek1 are required for proper meiotic recombination.…”
Section: Resultsmentioning
confidence: 99%
“…This phenotype is noteworthy considering that mek1Δ cells showed no delay in the initiation of meiotic S phase. 15 Next, we analyzed four mek1 mutants, mek1-KD (GP21), -FHAD (TT277), -T15A/KD (TT526) and -T15A/FHAD (TT548); the KD mutant lacks kinase activity and the FHAD mutant lacks the FHA domain function. Notably, the mek1-KD strain (GP21) was not delayed in meiosis (Sup.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations